PRODUCTION CAPACITY ENHANCEMENT AND APPLICATION TESTING OF MUTANT PETASE ENZYME ON PET PLASTIC - Humaira, Aisy
Polyethylene terephthalate (PET) is a type of plastic commonly used across various industrial sectors. The accumulation of PET waste in the environment poses health risks to living organisms and exacerbates ecological problems. One primary strategy to address the accumulation of PET waste is the development of enzymatic biodegradation methods, which break down PET polymers into monomers such as MHET, BHET, terephthalic acid, and ethylene glycol. This study aims to test a PETase enzyme that has undergone mutations at amino acid residues L117F, Q119Y, S121E, G165A, D186H, R280A, S214H, and S238F to enhance its thermostability and affinity for PET substrates. Previous laboratory-scale research optimized the expression of the mutant PETase enzyme in E. coli BL21(DE3), and this study aims to scale up production with culture volumes of 150 mL and 1 L. Transformed E. coli BL21(DE3) stock cultures were grown on solid LB media, and colony confirmation was performed using colony PCR. The mutant PETase enzyme was produced in a 150 mL culture using 0.25 mM IPTG at approximately 30°C for 24 hours with 150 rpm agitation and in a 1 L culture using a bioreactor with the same parameters and 1.5 vvm aeration. Samples were taken at 8, 12, 18, and 24 hours during the fermentation process. All samples were purified using a Ni-NTA column and analyzed via SDS-PAGE and western blot. The activity of the mutant PETase enzyme was tested using the p-NPB substrate and PET polymer at 50°C and pH 9. Electrophoresis results confirmed the presence of the pET22b(+) plasmid with the mutant PETase gene sized at 1210 bp. Expression of the mutant PETase enzyme in the 150 mL culture produced a protein of 30.7 kDa, while the 1 L culture produced a protein close to 40 kDa, as visualized by SDS-PAGE and western blot. Activity assays indicated that for crude enzyme, culture duration and volume influenced terephthalic acid concentration and enzyme activity, with the highest values on day 7 at 138.03 ppm and 140 ppm, and activity percentages of 41.46% and 42.174%. For purified freeze-dried enzyme, the highest concentrations reached 140.8 ppm and 143.94 ppm, with activity percentages of 42.2% and 43.1%. Incubation of PET with concentrated purified PETase enzyme showed that only incubation duration significantly affected terephthalic acid concentration, with the highest values at 145.14 ppm and 145.59 ppm, and activity percentages of 43.54% and 43.67% for both culture volumes. The conclusion of this study is that the mutant PETase enzyme can be successfully expressed on a larger scale with minimal characteristic differences. Incubation duration significantly impacts the terephthalic acid concentration produced, except for purified freeze-dried enzyme. Enzymes from different culture volumes showed significant differences in terephthalic acid concentration, except in samples incubated with concentrated purified enzyme. Further research is recommended to optimize production parameters on a 1 L scale, such as pH, aeration, and incubation time, to achieve maximum yield of the mutant PETase enzyme. Additionally, further enzyme characterization is necessary to understand the structural compatibility of the produced mutant PETase enzyme.